2003
DOI: 10.1046/j.1365-3156.2003.01071.x
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Comparison of serology and isolates for the identification of infecting leptospiral serogroups in Hawaii, 1979–1998

Abstract: SummaryLaboratory confirmation of leptospirosis is usually accomplished serologically, without isolates, using the microscopic agglutination test (MAT). However, optimal performance of the MAT is dependent on the knowledge of enzootic serogroups and serovars so that an appropriate MAT antigen testing battery can be established. Infecting leptospiral serogroups can be identified serologically without isolates, using the MAT, or by serogrouping of isolates, but little information is available regarding the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Individuals infected with serovar Copenhageni are expected to have serological cross-reactions against serovar Icterohaemorrhagiae since the both serovars belong to same serogroup [8]. Investigations performed in endemic areas in which several serogroups are circulating found that the predictive value of serology is low with respect to identifying the infecting serogroup [25],[26]. Our findings suggest that in a site where a single agent, serovar Copenhageni, is circulating, previously-infected individuals have agglutination titres which, even when low titres are encountered, are specifically directed against this serovar and serovars from the same serogroup.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals infected with serovar Copenhageni are expected to have serological cross-reactions against serovar Icterohaemorrhagiae since the both serovars belong to same serogroup [8]. Investigations performed in endemic areas in which several serogroups are circulating found that the predictive value of serology is low with respect to identifying the infecting serogroup [25],[26]. Our findings suggest that in a site where a single agent, serovar Copenhageni, is circulating, previously-infected individuals have agglutination titres which, even when low titres are encountered, are specifically directed against this serovar and serovars from the same serogroup.…”
Section: Discussionmentioning
confidence: 99%
“…Results from MAT testing of patient sera are used as a surrogate to infer the infecting serogroup. This approach may be unreliable (positive predictive value, 65-82%) [56,57]. Hence, there is an urgent need for improved typing tools.…”
Section: Serologic and Molecular Typingmentioning
confidence: 99%
“…This highsensitivity criterion is commonly used to define cases among ill patients in endemic or outbreak settings. 26,27 Patients with either a single MAT titer ≥ 800 for any serovar at either phase, or a serovar-specific four-fold increase from acute phase to convalescent phase with a minimum convalescent titer of 400, were categorized as definite leptospirosis. This definition is consistent with the strictest published serologic definitions.…”
mentioning
confidence: 99%